Análise faunísitica de besouros escarabeínos (Coleoptera : Scarabaeidae : Scarabaeinae) do monumento natural Grota do Angico, Sergipe, Brasil - Santos Júnior, José Francisco Gomes dos (2014)
The study of Caatinga is one of the biggest challenges for researchers of our country. Currently there are |islands| of preserved Caatinga in all its original territory extension, and fragmented environments leads to loss of biodiversity. Researchesoffaunistic analysismake possible to evaluate environmental impact, being frequently, accomplished with insects.In the group of bioindicators insects, dung beetles are scavengers that feed on feces, carcasses and decaying fruit, assisting in nutrient cycle and other ecological services. Therefore, the main goal of this study was to conduct a faunistic analysis of dung beetles occurring in Caatinga of the Sergipe state. It was studied the variation in dung beetles community in areas of Caatinga under two different preservation stages (protected and disturbed), and also the variation of dung beetles in three types of baits. The study was accomplishedat the MONA Grotaof Angico, located in the city of Poço Redondo, Sergipe, in the period of December 2012 to November 2013, in two areas of Caatinga: preserved and degraded. Ten sites weredelimited in each area, with 200 meters of distance from one site to the other. At each site,three pitfall traps were placed,with the following baits:human feces, banana and bovine liver. There were sampled 597 specimens distributed intwelve species and eleven genera. The species with higher abundance was Deltochilum verruciferumthat represented 80% of the specimens, being the only taxon classified as common, causing low equitability in the study. Malagoniella astyanax punctatostriata and Canthon mutabilis had, each one, only one specimen,throughout the study in the disturbed area. Dichotomius nisuspresented the higher number of sampled individuals in the disturbed area. The diversity among the areas did not differ significantly for Shannon index, but according to Simpson´sindex, thedisturbed area has a greater diversity. Jackknife pointed out that the two areas possess lower values than those estimated. The areas did not differ in richness,however the protected area, with 388 individuals, hadlarger dung beetles abundance than the disturbed area,with 209 collected individuals. There was not correlation between the monthly rainfalland the abundance of dung beetles. Regardingthe baits,always the bait of feces presented higher abundance and richness of these beetles, if compared to bananas and meat baits.